Nanoemulgel as an Efficacious Tool for the Aging Process - Mitali Singh; Zaira Hussain; Aafreen (Pharmaceutical Research - Recent Advances and Trends Vol. 3, 2024)
Becoming older is complicated and influenced by internal and external factors. A loss follows it in both the function and look of the skin as it progresses. One must look to cutting-edge approaches within the pharmaceutical and dermatological research communities to solve this complex challenge. The function of nanoemulgels as a potent weapon in the battle against skin ageing is thoroughly examined in this article. To develop effective treatments, it is essential to have an understanding of the processes that result in the ageing of the skin. The interaction of external factors like pollution, UV radiation, and lifestyle choices with intrinsic ones like biological processes and inheritance accelerates ageing. Nanoemulgels offer a better platform for accurately and successfully delivering anti-aging drugs due to the unique features that they possess. Utilizing nanoemulgels is the most current innovation in the fight against the signs of ageing skin that have been discovered. This article presents a comprehensive examination of their workings, including their benefits and limitations, the methods used to prepare them, and the variety of applications they find use in. Nanoemulgels show significant promise as a potential solution to the challenging issue of aging because of their capacity to deliver individualized treatments that are also very successful in preserving a youthful and healthy appearance of the skin.